HUBUNGAN KONDISI KANDANG TERNAK DENGAN KEJADIAN MALARIA DI DESA LAURI KECAMATAN GIDO KABUPATEN NIAS TAHUN 2013 - Siti Berlian Zebua; evi naria; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2014)
Malaria is a communicable disease which is still be a problem of public health in the world, including Indonesia. There are 42 districts / cities in Indonesia which  endemic of malaria. One of them is District of Nias. Annual Malaria Parasite in Nias reached 30.97 per 1000 population.This study used cross-sectional design with 64 samples of households. Sample was choosen based on specific criteria, that were who had cattle sheds. Data was analized using univariate and bivariate with Chi Square test or Fisher Exact.This study aims to determine the relationship between the condition of cattle sheds with malaria incidence at the community of Lauri village in sub-district of Gido Nias district in 2013.The results were based on bivariate analysis with a level of 95% and statistical tests showed that the ρ value of cattle sheds distance was 0.742 (ρ> 0.05),  ρ value of cattle sheds hygiene was 0.206 (ρ> 0.05), ρ value of puddles existence was 0.051 (ρ> 0.05) and ρ value of cage maintenance action was 0.97 (ρ> 0.05). that means there is no relationshipbetween the variables with malaria incidence.Based on the research results, it can be concluded that there is no relationship between the condition of cattle sheds with malaria incidence. Lauri village communities who have cattle sheds should pay more attention to the cleanliness of cattle sheds and surrounding areas.